a, rút gọn:
A=3.(2^2+1).(2^4+1)...(2^256+1)+1
b,CMR:
nếu (a+b+c)^2=3(a^2+b^2+c^2) thì a=b=c
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Bài 1:
Ta có: \(A=\left(2+1\right)\left(2^2+1\right)\left(2^4+1\right)...\left(2^{256}+1\right)+1\)
\(=\left(2-1\right)\left(2+1\right)\left(2^2+1\right)\left(2^4+1\right)...\left(2^{256}+1\right)+1\)
\(=\left(2^2-1\right)\left(2^2+1\right)\left(2^4+1\right)...\left(2^{256}+1\right)+1\)
\(=\left(2^4-1\right)\left(2^4+1\right)...\left(2^{256}+1\right)+1\)
\(............................\)
\(A=\left[\left(2^{256}\right)^2-1\right]+1=2^{512}\)
\(a,=x^3-16x-x^2-1-x^2+1=x^3-2x^2-16x\\ b,=y^4-81-y^4+4=-77\\ d,=a^2+b^2+c^2+2ab-2bc-2ac+a^2-2ac+c^2-2ab-2ac\\ =2a^2+b^2+2c^2-2bc-6ac\)